Implementation of Finger Print Electronic Absental Policy on Discipline and Performance of Civil Servants in The Government Office of Seluma Regency - Dian Setiawan (Ilomata International Journal of Management, 2020)
Describe the implementation of the fingerprint electronic absence policy on the discipline and performance of civil servants as well as the impact it has on implementing the fingerprint electronic absence policy. Qualitative descriptive method describes various conditions and situations as the object of research. The data collection techniques used were observation, documentation and interviews. After the implementation of fingerprint electronic attendance, discipline increases and obligations as employees have been carried out in accordance with applicable regulations. The application of sanctions in the regional government of seluma regency is in accordance with the regulations of civil servants and the provision of rewards for employees who excel has been carried out properly, to inspire other employees, so that they can work better.